Using Song Media in Civics Education to Enhance Diversity Awareness within The Bhinneka Tunggal Ika Framework at SD Muhammadiyah Jakarta - Wibawati, Kurnia Ary; Hadi, Muhamad Sofian (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
As educational institutions, schools play a pivotal role in fostering diversity awareness within the framework of "Bhinneka Tunggal Ika" (Unity in Diversity). Integrating education with the awareness of diversity can be effectively implemented through creative learning media, such as the song "Kita Beragam" (We Are Diverse), composed by teachers. This study aims to describe the use of song media in Pancasila and Citizenship Education to enhance students' awareness of societal and environmental diversity. The research adopts a qualitative, descriptive approach. Data collection methods included observation, interviews, and documentation. The study was conducted with 22 second-grade students at SD Muhammadiyah 41 Kayu Putih, East Jakarta. The findings suggest that song media can be an effective alternative to conventional teaching methods, which often result in monotonous learning experiences. The creative use of songs in the classroom can make the learning process more engaging, helping students better understand the lessons and improve learning outcomes. This study can serve as a reference for educators seeking innovative ways to enhance diversity education in Pancasila and Citizenship Education, particularly on the theme of diversity.